Development of parthenocarpic fruits in oil palm (Elaeis guineensis Jacq.) due to application of herbicides - Keong, Wan Chee (Incorporated Society of Planters, 1987)
A stand of three-year old palm (Elaeis guineensis Jacq.) were treated with picloram, glyphosate, 2, 4-D, garlon 250, lontrel, and starane to study their effects on the production of parthenocarpic fruits. Results from this study indicate that only picloram was effective in causing a significant amount of fruits in individual fruit bunches to develop parthenocarpically, The degree of parthen ocarpy observed in individual fruit bunches of palms treated with glyphosate, 2, 4-D, garlon 250, lontrel, and starane was similar to that exhibited by palms in the control plots. The amount of parthenocarpic fruits formed in those individual fruit bunches was less than 10 and could be considered to be insignificant.